Socioeconomic Status as a Predictor of School Dropout in High School Students - Rodriguez Triviño, José Alejandro (2024)
elationship between socioeconomic status and school dropout among high school students. The methodology used was quantitative, with a hypothetical-deductive approach and a non-experimental design. A population of 270 students was identified, from which a representative sample of 200 students was selected from a public school offering extraordinary education. Two specific questionnaires were designed: the first addresses the social factors that may influence students' educational experience, and the second focuses on identifying the causes and patterns of school dropout. The results show a direct connection between the variables; applying the Pseudo R-squared, the Nagelkerke value indicates a high incidence value of socioeconomic level in school dropout, highlighting the importance of improving the conditions of these students to avoid school dropout. In conclusion, school dropout is significantly influenced by socioeconomic level highlighting the need to address this level affecting vulnerable youth to prevent school dropout.